The state and industry in South Korea : the limits of the authoritarian state - Rhee, Jong-Chan, 1957- (Routledge, 2002)
The author examines the nature of Korea's `industrial miracle' and, in particular, the limitations of its authoritarian state as a vehicle for intervening in the market or for sponsoring liberal reform.